Accumulation curves of environmental DNA sequences predict coastal fish diversity in the coral triangle. Issue 1930 (8th July 2020) - Juhel, Jean-Baptiste; Utama, Rizkie S.; Marques, Virginie; Vimono, Indra B.; Sugeha, Hagi Yulia; Kadarusman,; Pouyaud, Laurent; Dejean, Tony; Mouillot, David; Hocdé, Régis
Abstract : Environmental DNA (eDNA) has the potential to provide more comprehensive biodiversity assessments, particularly for vertebrates in species-rich regions. However, this method requires the completeness of a reference database (i.e. a list of DNA sequences attached to each species), which is not currently achieved for many taxa and ecosystems. As an alternative, a range of operational taxonomic units (OTUs) can be extracted from eDNA metabarcoding. However, the extent to which the diversity of OTUs provided by a limited eDNA sampling effort can predict regional species diversity is unknown. Here, by modelling OTU accumulation curves of eDNA seawater samples across the Coral Triangle, we obtained an asymptote reaching 1531 fish OTUs, while 1611 fish species are recorded in the region. We also accurately predict ( R ² = 0.92) the distribution of species richness among fish families from OTU-based asymptotes. Thus, the multi-model framework of OTU accumulation curves extends the use of eDNA metabarcoding in ecology, biogeography and conservation.